Complex segregation analysis of craniomandibular osteopathy in Deutsch Drahthaar dogs. (January 2018) - Vagt, J.; Distl, O.
Highlights: Craniomandibular osteopathy (CMO) is a familial condition in Deutsch Drahthaar dogs. Complex segregation analyses did not confirm a Mendelian inheritance for CMO. Most likely more than one locus is involved in CMO. Breeding measures should take into account the complex genetics of CMO. Abstract: This study investigated familial relationships among Deutsch Drahthaar dogs with craniomandibular osteopathy and examined the most likely mode of inheritance. Sixteen Deutsch Drahthaar dogs with craniomandibular osteopathy were diagnosed using clinical findings, radiography or computed tomography. All 16 dogs with craniomandibular osteopathy had one common ancestor. Complex segregation analyses rejected models explaining the segregation of craniomandibular osteopathy through random environmental variation, monogenic inheritance or an additive sex effect. Polygenic and mixed major gene models sufficiently explained the segregation of craniomandibular osteopathy in the pedigree analysis and offered the most likely hypotheses. The SLC37A2:c. 1332C > T variant was not found in a sample of Deutsch Drahthaar dogs with craniomandibular osteopathy, nor in healthy controls. Craniomandibular osteopathy is an inherited condition in Deutsch Drahthaar dogs and the inheritance seems to be more complex than a simple Mendelian model.